2021
DOI: 10.3390/bios11010015
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Strategy for the Simultaneous Detection of Doxorubicin and Simvastatin for Their Potential Use in the Treatment of Cancer

Abstract: The aim of this study was to develop a disposable, simple, fast, and sensitive sensor for the simultaneous electrochemical detection of doxorubicin (DOX) and simvastatin (SMV), which could be used in preclinical studies for the development of new pharmaceutical formulations for drug delivery. Firstly, the electrochemical behavior of each molecule was analyzed regarding the influence of electrode material, electrolyte solution, and scan rate. After this, the proper electrode material, electrolyte solution, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…It must be underlined that in this situation, the diffusion rates of both DOX electrooxidation and electroreduction are almost similar in comparison with Cu/GRQD/CNT electrode. Taking into account the mechanisms suggested in the literature considering the reversible two electrons and two protons based DOX electrooxidation/electroreduction [10] and supplementary DOX electroreduction [13], which consider the conversion between quinone and a hydroquinone functional groups, and based on all above presented results, in this study the tentative global mechanism for DOX electrochemical oxidation and reduction is proposed in Figure 8. Taking into account the mechanisms suggested in the literature considering the reversible two electrons and two protons based DOX electrooxidation/electroreduction [10] and supplementary DOX electroreduction [13], which consider the conversion between quinone and a hydroquinone functional groups, and based on all above presented results, in this study the tentative global mechanism for DOX electrochemical oxidation and reduction is proposed in Figure 8.…”
Section: Mechanistic Aspects-influence Of the Scan Ratementioning
confidence: 98%
See 1 more Smart Citation
“…It must be underlined that in this situation, the diffusion rates of both DOX electrooxidation and electroreduction are almost similar in comparison with Cu/GRQD/CNT electrode. Taking into account the mechanisms suggested in the literature considering the reversible two electrons and two protons based DOX electrooxidation/electroreduction [10] and supplementary DOX electroreduction [13], which consider the conversion between quinone and a hydroquinone functional groups, and based on all above presented results, in this study the tentative global mechanism for DOX electrochemical oxidation and reduction is proposed in Figure 8. Taking into account the mechanisms suggested in the literature considering the reversible two electrons and two protons based DOX electrooxidation/electroreduction [10] and supplementary DOX electroreduction [13], which consider the conversion between quinone and a hydroquinone functional groups, and based on all above presented results, in this study the tentative global mechanism for DOX electrochemical oxidation and reduction is proposed in Figure 8.…”
Section: Mechanistic Aspects-influence Of the Scan Ratementioning
confidence: 98%
“…Taking into account the mechanisms suggested in the literature considering the reversible two electrons and two protons based DOX electrooxidation/electroreduction [10] and supplementary DOX electroreduction [13], which consider the conversion between quinone and a hydroquinone functional groups, and based on all above presented results, in this study the tentative global mechanism for DOX electrochemical oxidation and reduction is proposed in Figure 8. The occurrence of two reduction processes is evident for the Cu/GRQD/CNT paste electrode when analyzing the results of the scan rate influence with respect to higher slope for cathodic in comparison with anodic currents.…”
Section: Mechanistic Aspects-influence Of the Scan Ratementioning
confidence: 98%
“…Zhang et al (2009) conducted a subgroup analysis of the population who had previously received simvastatin and found that there was no significant difference in the risk of colorectal cancer among those who continued or stopped taking simvastatin, but the increase in serum cholesterol levels was independently associated with the risk reduction of colorectal cancer. We hypothesize that the idea that simvastatin reduces the risk of colorectal cancer in previous studies does not exclude the potential confounding effect of serum cholesterol prior to the use of simvastatin and that there may be concurrent use of simvastatin in people with a lower risk of cancer, which could lead to biased trial results and conclusions [ 34 ]. Clinical studies have confirmed that higher serum cholesterol levels can effectively reduce the risk of colorectal cancer.…”
Section: Exploration Of Simvastatin In the Treatment Of Colorectal Ca...mentioning
confidence: 99%
“…Therefore, the accurate detection of DOX concentration in serum and urine is of great significance, which can guide the dosage of DOX in a therapeutic process, minimizing the toxicity and side effects of DOX . The previously reported methods for the detection of DOX mainly involve high performance liquid chromatography (HPLC), electrochemical sensing, Raman spectroscopy, and fluorescence probe . Although these methods are sensitive to DOX detection, their application is usually limited by expensive instrument, lengthy testing process and complex operation.…”
Section: Introductionmentioning
confidence: 99%